Reward Strategy: A Case Study In Malaysia Service Industry - Ong, Tze San; Yip, Mei Theen; Teh, Boon Heng (2011)
Purpose-The prurpose of this paper is to contribute to the body of knowledge in the area of reward systems, particularly the total reward framework. The reward framework determined serve as the principal guideline for the small and medium enterprise in Malaysia. Design/Methodology/Approach-The paper used an intensive case study of two selected insurance companies, known as Agency A and Company B. The two companies are different in terms of their size and capital. Findings-The findings suggest that the use of financial and objective measures are the main concern in designing the reward systems of the organization, companies are gradually incorporated non-financial measures in their reward systems. Other remarkable findings include identical rewards are ties to different working nature which is found to be deviate from normal norms. Research Limitation/ Implications-The reward framework identified can be used as guideline for the small and medium enterprise in Malaysia to further understand the function of reward system, thus design and implementation their unique and attractive reward system.